PENGUKURAN EFISIENSI BUMD: STUDI EMPIRIK PDAM DI EKS-KARISIDENAN SURAKARTA - Muzakar Isa; Abu Bakar Akbar (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2012)
The purpose of this study was to analyze the level of efficiency in Ex-residency SurakartaPDAM. The samples were PDAM of Surakarta, Sukoharjo and Klaten. The sampling method isnon-probability sampling, with convenience sampling method. The data used are secondary data.The data consists of input variables and output variables. Input variables consist of 1) the numberof staff hours per month, 2) the amount of water usage per month, 3) the total expenditure permonth, and 4) the ratio of the number of employees of an educated scholar. While the outputvariables consist of 1) the number of subscribers per month, 2) the amount of revenue per month.Data collection used is documentation method. Data analysis tool used is DEA. Based on theanalysis concluded there is 1 taps that do not operate efficiently, namely PDAM Sukoharjo (92.70).